Blogging for women in agriculture - Montcho, Marthe (Technical Centre for Agricultural and Rural Cooperation, 2016)
Marthe Montcho tells us how she set up her blog in Benin to showcase agricultural innovations and raise the profile of women in the agriculture sector.